The Sense of Place in the Poetry of John Montague - Grgas, Stipe (Array, 1997)
The purpose of this paper is to articulate the "sense of place" that the author takes to be one of the distinguishing characteristics not only of Montague's work, but of a whole tradition within irish poetry. On the theoretical level it draws attention to the depreciation of spatiality in discussions of literature and targets a body of texts in which the human environment figures as one of its recurrent motifs. In regard to the broader field of British studies, the findings of the paper point to the need to inscribe differences within a subject which is all too often conceived of as a homogeneous entity.